The Birds, the Bees, and Kristeva: An Examination of Sexual Desire in the Nature Poetry of Daphne Marlatt, Robert Kroetsch, and Tim Lilburn - Whetter, Darryl (Studies in Canadian Literature)

(untitled) (None, 1996)
Julia Kristeva's conception of "poetic language" can be useful in illustrating how the provisionality of language expands the poem into a dialogical poetics. Poetic language reveals the heterogeneity of not only desire but also the speaking/desiring subject. In the poetry of Daphne Marlatt, Robert Kroetsch, and Tim Lilburn, the heterogeneity of desire clearly propels the poem into what Kristeva describes as "metaphorical shifting" through which metaphors and episodes conflate and become "carnivalesque."